A New Developed Airlift Reactor Integrated Settling Process and Its Application for Simultaneous Nitrification and Denitrification Nitrogen Removal. (15th July 2013) - Zhang, Tao; Wei, Chaohai
Abstract : This study presented the performance of simultaneous nitrification and denitrification (SND) process using a new developed hybrid airlift reactor which integrated the activated sludge reaction process in the airlift reactor and the sludge settling separation process in the clarifier. The proposed reactor was started up successfully after 76 days within which the COD and total nitrogen removal rate can reach over 90% and 76.3%, respectively. The effects of different COD/N and DO concentrations on the performance of reactor were investigated. It was found that the influent COD/N maintained at 10 was sufficient for SND and the optimum DO concentration for SND was in the range of 0.5 to 0.8 mg L −1 . Batch test demonstrated that both macroscopic environment caused by the spatial DO concentration difference and microscopic environment caused by the stratification of activated sludge may be responsible for the SND process in the reactor. The hybrid airlift reactor can accomplish SND process in a single reactor and in situ automatic separation of sludge; therefore, it may serve as a promising reactor in COD and nitrogen removal fields.